The Impact of Anger Control Training on Resiliency in Adolescents with Addiction Preparation - Fatemeh Rasouli (Drug Control Headquarters, Research and Education Office, 2011)
Objective: Aggression and acting out behaviors can lead to drug use and acceptance in deviated groups. This project had planned to determine the impact of anger control training on resiliency enhancement in high school boys. Method: design of this research was pre experimental with pre-test post-test kind by control group. Sample includes of 30 high school students (15 experiment group, 15 in control group) selected by cluster sampling method. The students were randomly assigned in two experimental and control groups the experimental group received 12 sessions (two session per week) anger control training program. Then post-test assessments were made in both groups. Connor-Davidson resilience scale, State-trait anger expression inventory and Iranian addiction preparation scale were applied to assess variables. Findings: the analysis of data clearly showed anger control training has had effectiveness in resiliency and reduction in getting addicted. Conclusion: research findings emphasize importance of anger control training which increases resiliency in adolescents who have preparation for addiction. By adopting such training approaches in children and adolescents, we can take an important step in reduction of drug abuse and addiction prevention in this population.